DAPATKAH KETAHANAN PANGAN MENURUNKAN TINGKAT KEMISKINAN ANTAR PROVINSI DI INDONESIA? - Jakaria; Chaniago, Nuraini (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study was conducted with the aim of analyzing food security (aspects of availability, affordability and utilization) affect the poverty rate between provinces in Indonesia; analyzing the effect of infrastructure in the fields of education, health, roads, electricity and clean water on the poverty rate between provinces in Indonesia; analyzing the effect of social safety networks on poverty rates between provinces in Indonesia and analyzing the effect of financial inclusion on poverty rates between provinces in Indonesia. The research design used is causality research, the sample design use purposive sampling with the number of cross section 34 provinces and time series period 2019-2024. The analytical tool used is panel regression. The findings show that food security is proven to be able to reduce poverty levels in Indonesia, the provision of infrastructure for electricity, water is proven to have a significant effect in reducing poverty levels. Social safety nets have been shown to significantly reduce poverty levels in Indonesia. Infrastructure in the fields of education, health and roads has not been able to reduce poverty rates between provinces in Indonesia. Financial inclusion has not been able to reduce poverty rates between provinces in Indonesia.